Integrated Justice System in an Unforeseen Contingency: Ensuring Compliance with Health Protocol in Bogor Regency - Akbar, Hafiz; Achjani Zulfa, Eva; Nita, Surya (Sekolah Tinggi Ilmu Kepolisian, 2024)
The government of West Java has applied discretion in interpreting the national disaster regulation through West Java Province Bylaw Number 5/2021. To ensure procedural justice for the society, the bylaw applies fines through a trial court of minor offenses against health protocols violators. The implementation of the bylaw is a manifestation of the theory of an integrated criminal justice system, which, to date, has only been carried out independently. However, in this case, there is an integration in achieving an objective of law enforcement, that is, the prevention of the spread of the pandemic. Thus, this study examines the implementation of the Bylaw involving Indonesian National Police and Civil Service Police in regulating the health protocol. This research uses descriptive qualitative methodology involving triangulation, literature reviews, interviews, and case studies. The results reveal that an integrated judicial system has been implemented and met its objective in ensuring public compliance to health protocols. Yet, a number of issues persists, including using quantitative performance metrics in identifying the target offenders, outdated paperwork methods, teleconferencing judicial processes that are hindered by the existing constitution, and dilemma in either imposing heavy fines or light fines in a society hit hard by an unseen contingency.